Corrigendum to “Modeling the hydrological impact of land use change in a dolomite dominated karst system” (Journal of Hydrology (2018) 567 (267–279), (S0022169418307789), (10.1016/j.jhydrol.2018.10.017)) - Bittner, Daniel; Sheikhy Narany, Tahoora; Kohl, Bernhard; Disse, Markus; Chiogna, Gabriele (Journal of Hydrology, 2020)
The authors regret incorrect attribution of the hydrotope mapping in the research paper (chapter ‘2.2. Hydrotopes’). The wrong sentence is: ‘A detailed field mapping campaign was carried out by Markart et al. (2012) following the method by Koeck and Hochbichler (2012).’ The corrected sentence including the correct attribution of the hydrotope mapping has to be: ‘A detailed field mapping campaign was carried out yielding the Forest Hydrotope Model data base and report. All subsequently mentioned hydrotope categories are part of this database (Koeck and Hochbichler, 2012).’ Citation: Koeck, R., Hochbichler, E. (2012). Das Wald-Hydrotop-Modell als WSMS-Werkzeug im Quellenschongebiet der Stadt Waidhofen/Ybbs. Report in the course of the Interreg SEE CC-WaterS project: https://www.bmnt.gv.at – search for: “ccwaters”. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2024-04-17